Fluoride effect on parameters related to glucose homeostasis in NOD mice: using proteomic analysis of liver and gastrocnemius muscle to unravel the underlying mechanisms - Trevizol, Juliana Sanches (2020)
Water fluoridation is an important public health measure for the control of dental caries. Recent animal studies have shown that low doses of fluoride (F) in the drinking water, similar to those found in public water supplies, increase insulin sensitivity and reduce blood glucose. In the present study we evaluated the effects of low-level F exposure through the drinking water on glucose homeostasis in female NOD mice. Seventy-two 6-week mice were randomly divided into 2 groups according to the concentration of F in the drinking water (0-control, or 10 mg/L) they received for 14 weeks. After the experimental period the blood was collected for analyses of plasma F, glucose and insulin. Liver and gastrocnemius muscle were collected for proteomic analysis. Plasma F concentrations were significantly higher in the F-treated than in the control group. Despite treatment with fluoridated water reduced plasma levels glucose by 20% compared to control, no significant differences were found between the groups for plasma glucose and insulin. In the muscle, treatment with fluoridated water increased the expression of proteins related to muscle contraction, while in the liver, there was an increase in expression of antioxidant proteins and in proteins related to carboxylic acid metabolic process. Remarkably, phosphoenolpyruvate carboxykinase (PEPCK) was found exclusively in the liver of control mice. The reduction in PEPCK, a positive regulator of gluconeogenesis, thus increasing glucose uptake, might be a probable mechanism to explain the anti-diabetic effects of low doses of F, which should be evaluated in further studies.